(3TQM GdehGba aj Yde GdcdGe ddEjLjs - (3GdLQLGfj, Ydj Hf eMeO Hf Ydj,, GdeYQha HGdTQja GdLQLGfj J (B816 (3g`s ((3MGLj HGTGs)
(3ChdgG (B:s
(3Vef NWHI cJGHg GdETGQI Edi GdebGUO Yde GdcdGe QYGjI dHQGYI GdGSJgdGd aSLd ChdG JjefG Ke bGd GdMeO ddg GdYdj TCfg s
(3BNQgG (B:s
(3HeNGdaJg hEf cGf bWYjG aajg NdGa hCeG eG YOGg aGdbGFd eHJOY ZjQ cGaQ hddabgGA aj ebGdJge NdGa gh NGQL Yf affG gPG bGd GdeUfa hdjcf gPG BNQ GdcdGe ef cJGH GdehGbas
(3aj Chdg agQS (B- (3efbhdI ef fSNI GdeDda GdeDQNI H (B807 (3g` HSeQbfOs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B5 / 7s
(3eYLe GdeDdajf (B2 / 515s
(3cTa GdXfhf (B2 / 1891s
(3gOjI GdYGQajf (B1 / 728s
Keywords: (3GdadSaI hGdefWbs